2023
DOI: 10.3389/fphar.2023.1203247
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanisms governing P01 scorpion toxin effect against U87 glioblastoma cells oncogenesis

Abstract: The emerging concept of small conductance Ca2+-activated potassium channels (SKCa) as pharmacological target for cancer treatment has significantly increased in recent years. In this study, we isolated the P01 toxin from Androctonus australis (Aa) scorpion venom and investigated its effect on biological properties of glioblastoma U87, breast MDA-MB231 and colon adenocarcinoma LS174 cancer cell lines. Our results showed that P01 was active only on U87 glioblastoma cells. It inhibited their proliferation, adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Our laboratory has described the role of plasma membrane SK3 in breast, melanoma, prostate, and colon cancer cell migration in vitro and in breast cancer metastasis in vivo [14 (p. 20), 15,21,24]. One recent article indicated that plasma membrane SK2 was responsible for pancreatic cancer cell migration and invasion [22] and involved in the proliferation of glioblastoma cells and in hypoxia-induced proliferation of melanoma cells [25,26]. To date, there is no data available on the role of SK2 channels in ovarian cancer cells and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has described the role of plasma membrane SK3 in breast, melanoma, prostate, and colon cancer cell migration in vitro and in breast cancer metastasis in vivo [14 (p. 20), 15,21,24]. One recent article indicated that plasma membrane SK2 was responsible for pancreatic cancer cell migration and invasion [22] and involved in the proliferation of glioblastoma cells and in hypoxia-induced proliferation of melanoma cells [25,26]. To date, there is no data available on the role of SK2 channels in ovarian cancer cells and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%